(untitled) (Medico Legal Update, 2020)
Modes of judicial execution of death sentence have to be determined in light of various objective factors like prevailing atmosphere of the international opinion, international norms and standards, contemporary penological theories and ever progressing standards of human decency. Though it’s essential to adapt the most civilized method of judicial execution, nevertheless, what is more important is how that civilized process of execution is carried out. History is witness to the fact that how medical professionals have made invaluable contributions to make the existing modes of execution more civilized, humane and efficient by playing the most pivotal role. Medicalization of the process of judicial execution through intravenous lethal injection is not novel. However, currently direct participation of physicians in the implementation of the death penalty through intravenous lethal injection has become an extremely controversial subject, initiating voluminous intellectual debate at global platforms. Hence, an appropriate contouring of such participation is increasingly coming under sharp scrutiny on ethical and legal grounds. The question arises, will the physicians not be guilty of gross professional misconduct by refusing to oversee the executions and taking care of the condemned persons in their last crucial hours, thereby neglecting their ethical responsibility to minimize the suffering and maximize the comfort. Physicians need to fulfill their role as caregivers by actively participating in the implementation and development of lethal injection as the most humane mode of judicial execution.